MORFOLOGI TELUR MEMPENGARUHI KUALITAS KUTHUK AYAM KAMPUNG GALLUS DOMESTICUS - Hikamah, Siti Roudlotul; Nurjanah, Umi; Sudiarti, Diah (Pendidikan Biologi,Universitas Islam Jember, 2014)
Gallus domesticus chicken is a favorite side dish of Indonesian society since the past until now, because the meat is delicious, low in cholesterol and fat, but rich in protein and carbohydrates. From the observation in Jember and surrounding areas, there is often a shortage of stock in the market because there are kuthuk often stunted and eventually die(lethal).The purpose of the study to determine the morphology of G. Domesticus ova that can produce the best quality kuthuk. The results are expected to contribute knowledge to the farmers in order to produce the best quality kuthuk, in order to get optimal benefits.This type of research is true experimental, with a sampling technique with simple random sampling. The design used was a completely randomized design (CRD) factorial using the first two factors form the egg, both kuthuk quality. Data from the study, tested with inferential statistics, namely ANOVA using SPSS v16. The analysis showed that, with the egg morphology of a large oval or flat smooth surface is great for the development of khutuk, small oval shape or a flat smooth surface good for kuthuk development, while large or small shapes with rough or uneven surfaces is not good to the development of Gallus domesticus kuthuk Keywords: Gallus domesticus, development, kuthuk.